Absolute, not relative brain size correlates with sociality in ground squirrels - Matějů, Jan; Kratochvíl, Lukáš; Pavelková, Zuzana; Pavelková Řičánková, Věra; Vohralík, Vladimír; Němec, Pavel (Proceedings - Royal Society. Biological sciences, 2016)
The social brain hypothesis (SBH) contends that cognitive demands associated with living in cohesive social groups favour the evolution of large brains. Although the correlation between relative brain size and sociality reported in various groups of birds and mammals provides broad empirical support for this hypothesis, it has never been tested in rodents, the largest mammalian order. Here, we test the predictions of the SBH in the ground squirrels from the tribe Marmotini. These rodents exhibit levels of sociality ranging from solitary and single-family female kin groups to egalitarian polygynous harems but feature similar ecologies and life-history traits. We found little support for the association between increase in sociality and increase in relative brain size. Thus, sociality does not drive the evolution of encephalization in this group of rodents, a finding inconsistent with the SBH. However, body mass and absolute brain size increase with sociality. These findings suggest that increased social complexity in the ground squirrels goes hand in hand with larger body mass and brain size, which are tightly coupled to each other.
Keywords: Animals; Sex Characteristics; mozek; Female; Social Behavior; mužské pohlaví; zvířata; biologická evoluce; velikost orgánu; Biological Evolution; Male; sociální chování; Brain; Sciuridae; pohlavní dimorfismus; ženské pohlaví; Organ Size